Parents’ linguistic strategies in interaction with their children with history of cleft lip and/or palate - Saad, Mohammad Azannee; Mohd Jan, Jariah; Wahid, Ridwan (Wiley-Blackwell, 2021)
Background: Cleft lip and/or palate (CL/P) presents a rather complex challenge that requires understanding beyond biological or clinical perspective. Even though inaccuracies in speech articulation are the common consequences of CL/P, individuals with repaired CL/P are likely to experience other language-associated issues. Studies on social interaction have generally reported the children to be passive interlocutors, despite having their surgical treatment at the early stages of life. Aims: This study aims to describe the linguistic strategies that parents employ when interacting with their repaired CL/P child. How parents allocate the next turn of speaking to their repaired CL/P child will be specifically examined. Methods & Procedures: Three parent–child pairs with each child having repaired CL/P were selected to participate in the study. Guided by the principles of Conversation Analysis, their everyday interactions in their homes were video-recorded and transcribed according to the Jefferson System of Transcription Notation (2004). The transcriptions were subsequently analysed in order to highlight the linguistic strategies. Outcomes & Results: Three main linguistic strategies are identified in the parents’ turns when they allocate the next turn of speaking to their repaired CL/P child. Specifically, parents’ turns are constructed through interrogative sentences in addition to using emphasis words and repeated elicitation of responses from their child. Conclusion & Implications: Parents’ linguistic strategies are found to be restrictive as they limit children’s active participation. Consequently, the interaction becomes asynchronous rather than synchronous, which could otherwise benefit children’s language development. Findings provide information on how parents can be supported in order to foster a positive growth of the children’s language development through everyday interactions.